Tackling nasal symptoms in athletes: Moving towards personalized medicine. Issue 9 (26th March 2021) - Hox, Valerie; Beyaert, Simon; Bullens, Dominique; Couto, Mariana; Langer, Daniel; Hellings, Peter‐Willem; Huart, Caroline; Rombaux, Philippe; Seys, Sven F.; Surda, Pavol; Walker, Abigail; Steelant, Brecht
Abstract: Adequate nasal breathing is indispensable for athletes, and nasal symptoms have been shown to interfere with their subjective feeling of comfortable breathing and quality of life. Nasal symptoms are caused by either structural abnormalities or mucosal pathology. Structural pathologies are managed differently from mucosal disease, and therefore, adequate diagnosis is of utmost importance in athletes in order to choose the correct treatment option for the individual. Literature suggests that nasal symptoms are more prevalent in athletes compared to the general population and certain sports environments might even trigger the development of symptoms. Given the high demands of respiratory function in athletes, insight into triggering factors is of high importance for disease prevention. Also, it has been suggested that athletes are more neglectful to their symptoms and hence remain undertreated, meaning that special attention should be paid to education of athletes and their caregivers. This review aims at giving an overview of nasal physiology in exercise as well as the possible types of nasal pathology. Additionally, diagnostic and treatment options are discussed and we focus on unmet needs for the management and prevention of these symptoms in athletes within the concept of precision medicine.